2020
DOI: 10.3389/fpls.2019.01765
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation in the Plant Response to Stress

Abstract: As sessile organisms, plants face a variety of environmental challenges. Their reproduction and survival depend on their ability to adapt to these stressors, which include water, heat stress, high salinity, and pathogen infection. Failure to adapt to these stressors results in programmed cell death and decreased viability, as well as reduced productivity in the case of crop plants. The growth and development of plants are maintained by meiosis and mitosis as well as endoreduplication, during which DNA replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 134 publications
4
111
0
Order By: Relevance
“…Among the MSA genes, six ribosomal subunit proteins are regulated by signaling molecules such as methyl jasmonate, salicylic acid and environmental stress e.g., cold, heat, UV, drought, salinity [88], [89]. Two cell cycle related MSA genes – cyclin-A and ‘APC10’ are involved in plant immunity, disease resistance as well as abiotic stress responses [90], [91].…”
Section: Resultsmentioning
confidence: 99%
“…Among the MSA genes, six ribosomal subunit proteins are regulated by signaling molecules such as methyl jasmonate, salicylic acid and environmental stress e.g., cold, heat, UV, drought, salinity [88], [89]. Two cell cycle related MSA genes – cyclin-A and ‘APC10’ are involved in plant immunity, disease resistance as well as abiotic stress responses [90], [91].…”
Section: Resultsmentioning
confidence: 99%
“…Sugars and CKs are fully part of the regulation of the dynamic balance between cell division and cell differentiation, which determines organ shape and size. Sugars can activate the expression of key cell cycle regulators, such as cyclin-dependent kinases (CDKs) and their interacting cyclins (CYCs), promoting the G2/mitosis transition in Arabidopsis seedling meristematic tissues [ 88 , 94 , 95 , 96 , 97 ]. CK signaling contributes to the stimulation of cell division and meristem initiation/formation [ 98 , 99 ].…”
Section: Meristem Establishment and Functioningmentioning
confidence: 99%
“…There are seven groups of CDKs (CDKA to CDKG) and seven classes of cyclins (CYC) in plants. In plants, the A, B and D cyclin classes have been defined [ 5 ]. The A-type cyclins are expressed during the S, G2 and M phases, while the B-type cyclins accumulate during the G2-M phases and regulate the entry into the M phase.…”
Section: Introductionmentioning
confidence: 99%
“…Both the biotic and abiotic stresses that affect plants can influence the cell cycle progression. It was shown that temperature stress arrests the cell cycle due to the reduced transcription of CYCA and CYCB and, as a result, decreased CDK activity [ 5 ]. In wheat seedlings that had been subjected to mild water stress, the mitotic activity was reduced in the mesophyll cells due to the decreased activity of CDKA1 , which is required for entry into mitosis [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%